Você está na página 1de 6

(𝒙) = 𝟕𝟑, 𝟕𝟓𝒌𝑵 ∙ 〈𝒙 − 𝟎𝒎〉−𝟏 −𝟏𝟐𝟎𝒌𝑵𝒎 ∙ 〈𝒙 − 𝟐𝒎〉−𝟐 −𝟒𝟓𝒌𝑵 ∙ 〈𝒙 − 𝟒𝒎〉−𝟏 −𝟑𝟎𝒌𝑵/𝒎 ∙ 〈𝒙 − 𝟔𝒎〉𝟎 +𝟑𝟎𝒌𝑵/𝒎 ∙ 〈𝒙 − 𝟗𝒎〉𝟎 +𝟔𝟏, 𝟐𝟓𝒌𝑵 ∙ 〈𝒙 − 𝟏𝟐𝒎〉−𝟏

𝑽(𝒙) = 𝟕𝟑, 𝟕𝟓𝒌𝑵 ∙ 〈𝒙 − 𝟎𝒎〉𝟎 −𝟏𝟐𝟎𝒌𝑵𝒎 ∙ 〈𝒙 − 𝟐𝒎〉−𝟏 −𝟒𝟓𝒌𝑵 ∙ 〈𝒙 − 𝟒𝒎〉𝟎 −𝟑𝟎𝒌𝑵/𝒎 ∙ 〈𝒙 − 𝟔𝒎〉𝟏 +𝟑𝟎𝒌𝑵/𝒎 ∙ 〈𝒙 − 𝟗𝒎〉𝟏 +𝟔𝟏, 𝟐𝟓𝒌𝑵 ∙ 〈𝒙 − 𝟏𝟐𝒎〉𝟎
𝑴(𝒙) = 𝟕𝟑, 𝟕𝟓𝒌𝑵 ∙ 〈𝒙 − 𝟎𝒎〉𝟏 −𝟏𝟐𝟎𝒌𝑵𝒎 ∙ 〈𝒙 − 𝟐𝒎〉𝟎 −𝟒𝟓𝒌𝑵 ∙ 〈𝒙 − 𝟒𝒎〉𝟏 −(𝟑𝟎𝒌𝑵/𝒎)/𝟐 ∙ 〈𝒙 − 𝟔𝒎〉𝟐 +(𝟑𝟎𝒌𝑵/𝒎)/𝟐 ∙ 〈𝒙 − 𝟗𝒎〉𝟐 +𝟔𝟏, 𝟐𝟓𝒌𝑵 ∙ 〈𝒙 − 𝟏𝟐𝒎〉𝟏
𝑉(𝑥) = 73,75 ∙ 〈𝑥 − 0〉0 −120 ∙ 〈𝑥 − 2〉−1 −45 ∙ 〈𝑥 − 4〉0 −30 ∙ 〈𝑥 − 6〉1 +30 ∙ 〈𝑥 − 9〉1 +61,25 ∙ 〈𝑥 − 12〉0
𝑥=0 𝑥=0 0≠2 0<4 0<6 0<9 0 < 12
∴ (𝑥 − 0)0 ∴ 〈𝑥 − 2〉−1 = 0 ∴ 〈𝑥 − 4〉0 = 0 ∴ 〈𝑥 − 6〉1 = 0 ∴ 〈𝑥 − 9〉1 = 0 ∴ 〈𝑥 − 12〉0 = 0
𝑉(𝑥) = 73,75 ∙ 1
73,75𝑘𝑁
𝑥<4 4>0 4≠2 𝑥<4 4< 6 4<9 4 < 12
∴ (𝑥 − 0)0 ∴ 〈𝑥 − 2〉−1 = 0 ∴ 〈𝑥 − 4〉0 = 0 ∴ 〈𝑥 − 6〉1 = 0 ∴ 〈𝑥 − 9〉1 = 0 ∴ 〈𝑥 − 12〉0 = 0
𝑉(𝑥) = 73,75 ∙ 1
73,75𝑘𝑁
𝑥=4 4>0 4≠2 𝑥=4 4< 6 4<9 4 < 12
∴ (𝑥 − 0)0 ∴ 〈𝑥 − 2〉−1 = 0 ∴ (𝑥 − 4)0 ∴ 〈𝑥 − 6〉1 = 0 ∴ 〈𝑥 − 9〉1 = 0 ∴ 〈𝑥 − 12〉0 = 0
𝑉(𝑥) = 73,75 ∙ 1 −45 ∙ 1
73,75 ∙ 1 − 45 ∙ 1 = 28,75𝑘𝑁
𝑥<6 6>0 6≠2 6>4 𝑥<6 6< 9 6< 12
∴ (𝑥 − 0)0 ∴ 〈𝑥 − 2〉−1 = 0 ∴ (𝑥 − 4)0 ∴ 〈𝑥 − 6〉1 = 0 ∴ 〈𝑥 − 9〉1 = 0 ∴ 〈𝑥 − 12〉0 = 0
𝑉(𝑥) = 73,75 ∙ 1 −45 ∙ 1
73,75 ∙ 1 − 45 ∙ 1 = 28,75𝑘𝑁
𝑥=6 6>0 6≠2 6>4 𝑥=6 6< 9 6< 12
∴ (𝑥 − 0)0 ∴ 〈𝑥 − 2〉−1 = 0 ∴ (𝑥 − 4)0 ∴ (𝑥 − 6)1 ∴ 〈𝑥 − 9〉1 = 0 ∴ 〈𝑥 − 12〉0 = 0
𝑉(𝑥) = 73,75 ∙ 1 −45 ∙ 1 −30 ∙ (𝑥 − 6)1
1
73,75 ∙ 1 − 45 ∙ 1 − 30 ∙ (𝑥 − 6) = 208,75 − 30 ∙ 𝑥
𝑥<9 9>0 9≠2 9>4 9>6 𝑥<9 9< 12
∴ (𝑥 − 0)0 ∴ 〈𝑥 − 2〉−1 = 0 ∴ (𝑥 − 4)0 ∴ (𝑥 − 6)1 ∴ 〈𝑥 − 9〉1 = 0 ∴ 〈𝑥 − 12〉0 = 0
𝑉(𝑥) = 73,75 ∙ 1 −45 ∙ 1 −30 ∙ (𝑥 − 6)1
1
73,75 ∙ 1 − 45 ∙ 1 − 30 ∙ (𝑥 − 6) = 208,75 − 30 ∙ 𝑥 𝑄𝑢𝑎𝑛𝑑𝑜 𝑉 = 0 , 𝑥 = 6,96𝑚
𝑥=9 9>0 9≠2 9>4 9>6 𝑥=9 9< 12
∴ (𝑥 − 0)0 ∴ 〈𝑥 − 2〉−1 = 0 ∴ (𝑥 − 4)0 ∴ (𝑥 − 6)1 ∴ (𝑥 − 9)1 ∴ 〈𝑥 − 12〉0 = 0
𝑉(𝑥) = 73,75 ∙ 1 −45 ∙ 1 −30 ∙ (𝑥 − 6)1 +30 ∙ (𝑥 − 9)1
1 1
73,75 ∙ 1 − 45 ∙ 1 − 30 ∙ (𝑥 − 6) + 30 ∙ (𝑥 − 9) = −61,25𝑘𝑁
𝑥 < 12 12 > 0 12 ≠ 2 12 > 4 12>6 12>9 𝑥 < 12
∴ (𝑥 − 0)0 ∴ 〈𝑥 − 2〉−1 = 0 ∴ (𝑥 − 4)0 ∴ (𝑥 − 6)1 ∴ (𝑥 − 9)1 ∴ 〈𝑥 − 12〉0 = 0
𝑉(𝑥) = 73,75 ∙ 1 −45 ∙ 1 −30 ∙ (𝑥 − 6)1 +30 ∙ (𝑥 − 9)1
(𝑥 1 (𝑥 1
73,75 ∙ 1 − 45 ∙ 1 − 30 ∙ − 6) + 30 ∙ − 9) = −61,25𝑘𝑁
𝑥 = 12 12 > 0 12 ≠ 2 12 > 4 12>6 12>9 𝑥 = 12
∴ (𝑥 − 0)0 ∴ 〈𝑥 − 2〉−1 = 0 ∴ (𝑥 − 4)0 ∴ (𝑥 − 6)1 ∴ (𝑥 − 9)1 ∴ 〈12 − 12〉0 = 1
𝑉(𝑥) = 73,75 ∙ 1 −45 ∙ 1 −30 ∙ (𝑥 − 6)1 +30 ∙ (𝑥 − 9)1 +61,25 ∙ 1
1 1
73,75 ∙ 1 − 45 ∙ 1 − 30 ∙ (𝑥 − 6) + 30 ∙ (𝑥 − 9) + 61,25 ∙ 1 = 0
𝑴(𝒙) = 𝟕𝟑, 𝟕𝟓 ∙ 〈𝒙 − 𝟎〉𝟏 −𝟏𝟐𝟎〈𝒙 − 𝟐〉𝟎 −𝟒𝟓 ∙ 〈𝒙 − 𝟒〉𝟏 −𝟏𝟓 ∙ 〈𝒙 − 𝟔〉𝟐 +𝟏𝟓 ∙ 〈𝒙 − 𝟗〉𝟐 +𝟔𝟏, 𝟐𝟓 ∙ 〈𝒙 − 𝟏𝟐〉𝟏
𝒙=𝟎 𝒙=𝟎 𝟎<𝟐 𝟎<𝟒 𝟎<𝟔 𝟎<𝟗 𝟎 < 𝟏𝟐
∴ (𝒙 − 𝟎)𝟏 ∴ 〈𝒙 − 𝟐〉𝟎 = 𝟎 ∴ 〈𝒙 − 𝟒〉𝟏 = 𝟎 ∴ 〈𝒙 − 𝟔〉𝟐 = 𝟎 ∴ 〈𝒙 − 𝟗〉𝟐 = 𝟎 ∴ 〈𝒙 − 𝟏𝟐〉𝟏 = 𝟎
𝑴(𝒙) = 𝟕𝟑, 𝟕𝟓 ∙ 𝟎
𝑴(𝟎𝒎) = 𝟎
𝒙<𝟐 𝟐>𝟎 𝒙<𝟐 𝟐<𝟒 2< 𝟔 𝟐<𝟗 𝟐 < 𝟏𝟐
∴ (𝒙 − 𝟎)𝟏 ∴ 〈𝒙 − 𝟐〉𝟎 = 𝟎 ∴ 〈𝒙 − 𝟒〉𝟏 = 𝟎 ∴ 〈𝒙 − 𝟔〉𝟐 = 𝟎 ∴ 〈𝒙 − 𝟗〉𝟐 = 𝟎 ∴ 〈𝒙 − 𝟏𝟐〉𝟏 = 𝟎
𝑴(𝒙) = 𝟕𝟑, 𝟕𝟓 ∙ 𝒙
𝟕𝟑, 𝟕𝟓 ∙ 𝒙 𝑴(𝒙 = 𝟏𝒎) = 𝟕𝟑, 𝟕𝟓𝒌𝑵𝒎 ; 𝑴(𝒙 = 𝟐𝒎) = 𝟏𝟒𝟕, 𝟓𝟎𝒌𝑵𝒎
𝒙=𝟐 𝟐>𝟎 𝒙=𝟐 𝟐<𝟒 2< 𝟔 𝟐<𝟗 𝟐 < 𝟏𝟐
∴ (𝒙 − 𝟎)𝟏 ∴ 〈𝒙 − 𝟐〉𝟎 = 𝟏 ∴ 〈𝒙 − 𝟒〉𝟏 = 𝟎 ∴ 〈𝒙 − 𝟔〉𝟐 = 𝟎 ∴ 〈𝒙 − 𝟗〉𝟐 = 𝟎 ∴ 〈𝒙 − 𝟏𝟐〉𝟏 = 𝟎
𝑴(𝒙) = 𝟕𝟑, 𝟕𝟓 ∙ 𝒙 −𝟏𝟐𝟎 ∙ 𝟏
𝟕𝟑, 𝟕𝟓 ∙ 𝒙 − 𝟏𝟐𝟎 𝑴(𝟐𝒎) = 𝟐𝟕, 𝟓𝟎𝒌𝑵𝒎
𝒙<𝟒 𝟒>𝟎 𝟒>𝟐 𝒙<𝟒 4< 𝟔 𝟒<𝟗 𝟒 < 𝟏𝟐
∴ (𝒙 − 𝟎)𝟏 ∴ 〈𝒙 − 𝟐〉𝟎 = 𝟏 ∴ 〈𝒙 − 𝟒〉𝟏 = 𝟎 ∴ 〈𝒙 − 𝟔〉𝟐 = 𝟎 ∴ 〈𝒙 − 𝟗〉𝟐 = 𝟎 ∴ 〈𝒙 − 𝟏𝟐〉𝟏 = 𝟎
𝑴(𝒙) = 𝟕𝟑, 𝟕𝟓 ∙ 𝒙 −𝟏𝟐𝟎 ∙ 𝟏
𝟕𝟑, 𝟕𝟓 ∙ 𝒙 − 𝟏𝟐𝟎 𝑴(𝟑𝒎) = 𝟏𝟎𝟏, 𝟐𝟓𝒌𝑵𝒎 ; 𝑴(𝟒𝒎) = 𝟏𝟕𝟓, 𝟎𝟎𝒌𝑵𝒎
𝒙=𝟒 𝟒>𝟎 𝟒>𝟐 𝒙=𝟒 4< 𝟔 𝟒<𝟗 𝟒 < 𝟏𝟐
∴ (𝒙 − 𝟎)𝟏 ∴ 〈𝒙 − 𝟐〉𝟎 = 𝟏 ∴ (𝒙 − 𝟒)𝟏 ∴ 〈𝒙 − 𝟔〉𝟐 = 𝟎 ∴ 〈𝒙 − 𝟗〉𝟐 = 𝟎 ∴ 〈𝒙 − 𝟏𝟐〉𝟏 = 𝟎
𝑴(𝒙) = 𝟕𝟑, 𝟕𝟓 ∙ 𝒙 −𝟏𝟐𝟎 ∙ 𝟏 −𝟒𝟓 ∙ (𝒙 − 𝟒)𝟏
𝟕𝟑, 𝟕𝟓 ∙ 𝒙 − 𝟏𝟐𝟎 − 𝟒𝟓 ∙ (𝒙 − 𝟒)𝟏 = 𝟐𝟖, 𝟕𝟓 ∙ 𝒙 + 𝟔𝟎 𝑴(𝟒𝒎) = 𝟏𝟕𝟓, 𝟎𝟎𝒌𝑵𝒎
𝒙<𝟔 𝟔>𝟎 𝟔>𝟐 𝟔>𝟒 𝒙<𝟔 6< 𝟗 6< 𝟏𝟐
∴= (𝒙 − 𝟎)𝟏 ∴ 〈𝒙 − 𝟐〉𝟎 = 𝟏 ∴ (𝒙 − 𝟒)𝟏 ∴ 〈𝒙 − 𝟔〉𝟐 = 𝟎 ∴ 〈𝒙 − 𝟗〉𝟐 = 𝟎 ∴ 〈𝒙 − 𝟏𝟐〉𝟏 = 𝟎
𝑴(𝒙) = 𝟕𝟑, 𝟕𝟓 ∙ 𝒙 −𝟏𝟐𝟎 ∙ 𝟏 −𝟒𝟓 ∙ (𝒙 − 𝟒)𝟏
𝟕𝟑, 𝟕𝟓 ∙ 𝒙 − 𝟏𝟐𝟎 − 𝟒𝟓 ∙ (𝒙 − 𝟒)𝟏 = 𝟐𝟖, 𝟕𝟓 ∙ 𝒙 + 𝟔𝟎 𝑴(𝟓𝒎) = 𝟐𝟎𝟑, 𝟕𝟓𝒌𝑵𝒎 ; 𝑴(𝟔𝒎) = 𝟐𝟑𝟐, 𝟓𝟎𝒌𝑵𝒎
𝒙=𝟔 𝟔>𝟎 𝟔>𝟐 𝟔>𝟒 𝒙=𝟔 6< 𝟗 6< 𝟏𝟐
∴ (𝒙 − 𝟎)𝟏 ∴ 〈𝒙 − 𝟐〉𝟎 = 𝟏 ∴ (𝒙 − 𝟒)𝟏 ∴ (𝒙 − 𝟔)𝟐 ∴ 〈𝒙 − 𝟗〉𝟐 = 𝟎 ∴ 〈𝒙 − 𝟏𝟐〉𝟏 = 𝟎
𝑴(𝒙) = 𝟕𝟑, 𝟕𝟓 ∙ 𝒙 −𝟏𝟐𝟎 ∙ 𝟏 −𝟒𝟓 ∙ (𝒙 − 𝟒)𝟏 −𝟏𝟓 ∙ (𝒙 − 𝟔)𝟐
𝟏 𝟐 𝟐
𝟕𝟑, 𝟕𝟓 ∙ 𝒙 − 𝟏𝟐𝟎 − 𝟒𝟓 ∙ (𝒙 − 𝟒) − 𝟏𝟓 ∙ (𝒙 − 𝟔) = 𝟏𝟓 ∙ (−𝒙 + 𝟏𝟑, 𝟗𝟏𝟔𝟕 ∙ 𝒙 − 𝟑𝟐) 𝑴(𝟔𝒎) = 𝟐𝟑𝟐, 𝟓𝟎𝒌𝑵𝒎
𝒙<𝟗 𝟗>𝟎 𝟗>𝟐 𝟗>𝟒 𝟗>𝟔 𝒙<𝟗 9< 𝟏𝟐
∴ (𝒙 − 𝟎)𝟏 ∴ 〈𝒙 − 𝟐〉𝟎 = 𝟏 ∴ (𝒙 − 𝟒)𝟏 ∴ (𝒙 − 𝟔)𝟐 ∴ 〈𝒙 − 𝟗〉𝟐 = 𝟎 ∴ 〈𝒙 − 𝟏𝟐〉𝟏 = 𝟎
𝑴(𝒙) = 𝟕𝟑, 𝟕𝟓 ∙ 𝒙 −𝟏𝟐𝟎 ∙ 𝟏 −𝟒𝟓 ∙ (𝒙 − 𝟒)𝟏 −𝟏𝟓 ∙ (𝒙 − 𝟔)𝟐
𝟏 𝟐 𝟐
𝟕𝟑, 𝟕𝟓 ∙ 𝒙 − 𝟏𝟐𝟎 − 𝟒𝟓 ∙ (𝒙 − 𝟒) − 𝟏𝟓 ∙ (𝒙 − 𝟔) = 𝟏𝟓 ∙ (−𝒙 + 𝟏𝟑, 𝟗𝟏𝟔𝟕 ∙ 𝒙 − 𝟑𝟐) 𝑴(𝟔, 𝟗𝟔𝒎) = 𝟐𝟒𝟔, 𝟐𝟖𝒌𝑵𝒎; 𝑴(𝟖𝒎) = 𝟐𝟑𝟎𝒌𝑵𝒎
𝒙=𝟗 𝟗>𝟎 𝟗>𝟐 𝟗>𝟒 𝟗>𝟔 𝒙=𝟗 9< 𝟏𝟐
∴ (𝒙 − 𝟎)𝟏 ∴ 〈𝒙 − 𝟐 〉𝟎 = 𝟏 ∴ (𝒙 − 𝟒)𝟏 ∴ (𝒙 − 𝟔)𝟐 ∴ (𝒙 − 𝟗)𝟐 ∴ 〈𝒙 − 𝟏𝟐〉𝟏 = 𝟎
𝑴(𝒙) = 𝟕𝟑, 𝟕𝟓 ∙ 𝒙 −𝟏𝟐𝟎 ∙ 𝟏 −𝟒𝟓 ∙ (𝒙 − 𝟒)𝟏 −𝟏𝟓 ∙ (𝒙 − 𝟔)𝟐 +𝟏𝟓 ∙ (𝒙 − 𝟗)𝟐
𝟏 𝟐 𝟐
𝟕𝟑, 𝟕𝟓 ∙ 𝒙 − 𝟏𝟐𝟎 − 𝟒𝟓 ∙ (𝒙 − 𝟒) − 𝟏𝟓 ∙ (𝒙 − 𝟔) + 𝟏𝟓 ∙ (𝒙 − 𝟗) = −𝟔𝟑, 𝟐𝟓 ∙ 𝒙 + 𝟕𝟑𝟓 𝑴(𝟗𝒎) = 𝟏𝟖𝟑, 𝟕𝟓𝒌𝑵𝒎
𝒙 < 𝟏𝟐 𝟏𝟐 > 𝟎 𝟏𝟐 > 𝟐 𝟏𝟐 > 𝟒 𝟏𝟐 > 𝟔 𝟏𝟐 > 𝟗 𝒙 < 𝟏𝟐
∴ (𝒙 − 𝟎)𝟏 ∴ 〈𝒙 − 𝟐〉𝟎 = 𝟏 ∴ (𝒙 − 𝟒)𝟏 ∴ (𝒙 − 𝟔)𝟐 ∴ (𝒙 − 𝟗)𝟐 ∴ 〈𝒙 − 𝟏𝟐〉𝟏 = 𝟎
𝑴(𝒙) = 𝟕𝟑, 𝟕𝟓 ∙ 𝒙 −𝟏𝟐𝟎 ∙ 𝟏 −𝟒𝟓 ∙ (𝒙 − 𝟒)𝟏 −𝟏𝟓 ∙ (𝒙 − 𝟔)𝟐 +𝟏𝟓 ∙ (𝒙 − 𝟗)𝟐
𝟕𝟑, 𝟕𝟓 ∙ 𝒙 − 𝟏𝟐𝟎 − 𝟒𝟓 ∙ (𝒙 − 𝟒)𝟏 − 𝟏𝟓 ∙ (𝒙 − 𝟔)𝟐 + 𝟏𝟓 ∙ (𝒙 − 𝟗)𝟐 = −𝟔𝟑, 𝟐𝟓 ∙ 𝒙 + 𝟕𝟑𝟓 𝑴(𝟏𝟎𝒎) = 𝟏𝟐𝟐, 𝟓𝟎𝒌𝑵𝒎; 𝑴(𝟏𝟏𝒎) = 𝟔𝟏, 𝟐𝟓𝒌𝑵𝒎
𝒙 = 𝟏𝟐 𝟏𝟐 > 𝟎 𝟏𝟐 > 𝟐 𝟏𝟐 > 𝟒 𝟏𝟐 > 𝟔 𝟏𝟐 > 𝟗 𝒙 = 𝟏𝟐
∴ (𝒙 − 𝟎)𝟏 ∴ 〈𝒙 − 𝟐〉𝟎 = 𝟏 ∴ (𝒙 − 𝟒)𝟏 ∴ (𝒙 − 𝟔)𝟐 ∴ (𝒙 − 𝟗)𝟐 ∴ 〈𝟏𝟐 − 𝟏𝟐〉𝟏 = 𝟎
𝑴(𝒙) = 𝟕𝟑, 𝟕𝟓 ∙ 𝒙 −𝟏𝟐𝟎 ∙ 𝟏 −𝟒𝟓 ∙ (𝒙 − 𝟒)𝟏 −𝟏𝟓 ∙ (𝒙 − 𝟔)𝟐 +𝟏𝟓 ∙ (𝒙 − 𝟗)𝟐 +𝟔𝟏, 𝟐𝟓 ∙ 𝟎
𝟏 𝟐 𝟐
𝟕𝟑, 𝟕𝟓 ∙ 𝒙 − 𝟏𝟐𝟎 − 𝟒𝟓 ∙ (𝒙 − 𝟒) − 𝟏𝟓 ∙ (𝒙 − 𝟔) + 𝟏𝟓 ∙ (𝒙 − 𝟗) = −𝟔𝟑, 𝟐𝟓 ∙ 𝒙 + 𝟕𝟑𝟓 𝑴(𝟏𝟐𝒎) = 𝟎
𝒅𝟐 𝒗 𝟑𝟎 𝟑𝟎
(𝑬 ∙ 𝑰) ∙ 𝟐
= 𝑴(𝒙) = 𝟕𝟑, 𝟐𝟓 ∙ 〈𝒙 − 𝟎〉𝟏 − 𝟏𝟐𝟎 ∙ 〈𝒙 − 𝟐〉𝟎 − 𝟒𝟓 ∙ 〈𝒙 − 𝟒〉𝟏 − ∙ 〈𝒙 − 𝟔〉𝟐 + ∙ 〈𝒙 − 𝟗〉𝟐 + 𝟔𝟏, 𝟐𝟓 ∙ 〈𝒙 − 𝟏𝟐〉𝟏
𝒅𝒙 𝟐 𝟐
𝒅𝒗 〈𝒙 − 𝟎〉𝟐 〈𝒙 − 𝟒〉𝟐 𝟑𝟎 〈𝒙 − 𝟔〉𝟑 𝟑𝟎 〈𝒙 − 𝟗〉𝟑 〈𝒙 − 𝟏𝟐〉𝟐
(𝑬 ∙ 𝑰) ∙ = 𝟕𝟑, 𝟐𝟓 ∙ − 𝟏𝟐𝟎 ∙ 〈𝒙 − 𝟐〉𝟏 − 𝟒𝟓 ∙ − ∙ + ∙ + 𝟔𝟏, 𝟐𝟓 ∙ + 𝑪𝟏
𝒅𝒙 𝟐 𝟐 𝟐 𝟑 𝟐 𝟑 𝟐
𝟕𝟑, 𝟐𝟓 〈𝒙 − 𝟎〉𝟑 〈𝒙 − 𝟐〉𝟐 𝟒𝟓 〈𝒙 − 𝟒〉𝟑 𝟑𝟎 〈𝒙 − 𝟔〉𝟒 𝟑𝟎 〈𝒙 − 𝟗〉𝟒 𝟔𝟏, 𝟐𝟓 〈𝒙 − 𝟏𝟐〉𝟑
(𝑬 ∙ 𝑰) ∙ 𝒗 = ∙ − 𝟏𝟐𝟎 ∙ − ∙ − ∙ + ∙ + ∙ + 𝑪𝟏 ∙ 𝒙 + 𝑪𝟐
𝟐 𝟑 𝟐 𝟐 𝟑 𝟔 𝟒 𝟔 𝟒 𝟐 𝟑

𝒅𝟐 𝒗 𝟑𝟎 𝟑𝟎
(𝑬 ∙ 𝑰) ∙ 𝟐
= 𝑴(𝒙) = 𝟕𝟑, 𝟐𝟓 ∙ 〈𝒙 − 𝟎〉𝟏 − 𝟏𝟐𝟎 ∙ 〈𝒙 − 𝟐〉𝟎 − 𝟒𝟓 ∙ 〈𝒙 − 𝟒〉𝟏 − ∙ 〈𝒙 − 𝟔〉𝟐 + ∙ 〈𝒙 − 𝟗〉𝟐 + 𝟔𝟏, 𝟐𝟓 ∙ 〈𝒙 − 𝟏𝟐〉𝟏
𝒅𝒙 𝟐 𝟐

𝒅𝒗 〈𝒙 − 𝟎〉𝟐 〈𝒙 − 𝟒〉𝟐 𝟑𝟎 〈𝒙 − 𝟔〉𝟑 𝟑𝟎 〈𝒙 − 𝟗〉𝟑 〈𝒙 − 𝟏𝟐〉𝟐


(𝑬 ∙ 𝑰) ∙ = 𝟕𝟑, 𝟐𝟓 ∙ − 𝟏𝟐𝟎 ∙ 〈𝒙 − 𝟐〉𝟏 − 𝟒𝟓 ∙ − ∙ + ∙ + 𝟔𝟏, 𝟐𝟓 ∙ + 𝑪𝟏
𝒅𝒙 𝟐 𝟐 𝟐 𝟑 𝟐 𝟑 𝟐

𝟕𝟑, 𝟐𝟓 〈𝒙 − 𝟎〉𝟑 〈𝒙 − 𝟐〉𝟐 𝟒𝟓 〈𝒙 − 𝟒〉𝟑 𝟑𝟎 〈𝒙 − 𝟔〉𝟒 𝟑𝟎 〈𝒙 − 𝟗〉𝟒 𝟔𝟏, 𝟐𝟓 〈𝒙 − 𝟏𝟐〉𝟑


(𝑬 ∙ 𝑰) ∙ 𝒗 = ∙ − 𝟏𝟐𝟎 ∙ − ∙ − ∙ + ∙ + ∙ + 𝑪𝟏 ∙ 𝒙 + 𝑪𝟐
𝟐 𝟑 𝟐 𝟐 𝟑 𝟔 𝟒 𝟔 𝟒 𝟐 𝟑

𝟕𝟑, 𝟐𝟓 𝟒𝟓 𝟓 𝟓 𝟔𝟏, 𝟐𝟓
(𝑬 ∙ 𝑰) ∙ 𝒗 = ∙ 〈𝒙 − 𝟎〉𝟑 − 𝟔𝟎 ∙ 〈𝒙 − 𝟐〉𝟐 − ∙ 〈𝒙 − 𝟒〉𝟑 − ∙ 〈𝒙 − 𝟔〉𝟒 + ∙ 〈𝒙 − 𝟗〉𝟒 + ∙ 〈𝒙 − 𝟏𝟐〉𝟑 + 𝑪𝟏 ∙ 𝒙 + 𝑪𝟐
𝟔 𝟔 𝟒 𝟒 𝟔

𝑷𝒂𝒓𝒂 𝒙 = 𝟎 → 𝒗 = 𝟎
𝟕𝟑, 𝟐𝟓 𝟒𝟓 𝟓 𝟓 𝟔𝟏, 𝟐𝟓
(𝑬 ∙ 𝑰) ∙ 𝒗 = ∙ 〈𝒙 − 𝟎〉𝟑 − 𝟔𝟎 ∙ 〈𝒙 − 𝟐〉𝟐 − ∙ 〈𝒙 − 𝟒〉𝟑 − ∙ 〈𝒙 − 𝟔〉𝟒 + ∙ 〈𝒙 − 𝟗〉𝟒 + ∙ 〈𝒙 − 𝟏𝟐〉𝟑 + 𝑪𝟏 ∙ 𝒙 + 𝑪𝟐
𝟔 𝟔 𝟒 𝟒 𝟔
𝟎 = 𝟎 ; 𝟎 < 𝟐 ; 𝟎 < 𝟒 ; 𝟎 < 𝟔 ; 𝟎 < 𝟗 ; 𝟎 < 𝟏𝟐
𝟕𝟑, 𝟐𝟓 𝟒𝟓 𝟓 𝟓 𝟔𝟏, 𝟐𝟓
(𝑬 ∙ 𝑰) ∙ 𝟎 = ∙ (𝟎 − 𝟎)𝟑 − 𝟔𝟎 ∙ 𝟎 − ∙𝟎− ∙𝟎+ ∙𝟎+ ∙ 𝟎 + 𝑪𝟏 ∙ 𝟎 + 𝑪𝟐
𝟔 𝟔 𝟒 𝟒 𝟔
∴ 𝑪𝟐 = 𝟎
𝑷𝒂𝒓𝒂 𝒙 = 𝟏𝟐 → 𝒗 = 𝟎
𝟕𝟑, 𝟐𝟓 𝟑 𝟐
𝟒𝟓 𝟓 𝟓 𝟔𝟏, 𝟐𝟓
(𝑬 ∙ 𝑰) ∙ 𝒗 = ∙ 〈𝒙 − 𝟎〉 − 𝟔𝟎 ∙ 〈𝒙 − 𝟐〉 − ∙ 〈𝒙 − 𝟒〉𝟑 − ∙ 〈𝒙 − 𝟔〉𝟒 + ∙ 〈𝒙 − 𝟗〉𝟒 + ∙ 〈𝒙 − 𝟏𝟐〉𝟑 + 𝑪𝟏 ∙ 𝒙 + 𝑪𝟐
𝟔 𝟔 𝟒 𝟒 𝟔
𝟏𝟐 > 𝟎 ; 𝟏𝟐 > 𝟐 ; 𝟏𝟐 > 𝟒 ; 𝟏𝟐 > 𝟔 ; 𝟏𝟐 > 𝟗 ; 𝟏𝟐 = 𝟏𝟐
𝟕𝟑, 𝟐𝟓 𝟒𝟓 𝟓 𝟓 𝟔𝟏, 𝟐𝟓
(𝑬 ∙ 𝑰) ∙ 𝟎 = ∙ (𝟏𝟐 − 𝟎)𝟑 − 𝟔𝟎 ∙ (𝟏𝟐 − 𝟐)𝟐 − ∙ (𝟏𝟐 − 𝟒)𝟑 − ∙ (𝟏𝟐 − 𝟔)𝟒 + ∙ (𝟏𝟐 − 𝟗)𝟒 + ∙ (𝟏𝟐 − 𝟏𝟐)𝟑 + 𝑪𝟏 ∙ 𝟏𝟐 + 𝟎
𝟔 𝟔 𝟒 𝟒 𝟔
𝟕𝟑, 𝟐𝟓 𝟒𝟓 𝟓 𝟓 𝟔𝟏, 𝟐𝟓
𝟎= ∙ (𝟏𝟐)𝟑 − 𝟔𝟎 ∙ (𝟏𝟎)𝟐 − ∙ (𝟖)𝟑 − ∙ (𝟔)𝟒 + ∙ (𝟑)𝟒 + ∙ (𝟎)𝟑 + 𝑪𝟏 ∙ 𝟏𝟐
𝟔 𝟔 𝟒 𝟒 𝟔
∴ 𝑪𝟏 = 𝟖𝟏𝟏, 𝟒𝟑𝟕𝟓

𝟕𝟑, 𝟐𝟓 𝟒𝟓 𝟓 𝟓 𝟔𝟏, 𝟐𝟓
(𝑬 ∙ 𝑰) ∙ 𝒗 = ∙ 〈𝒙 − 𝟎〉𝟑 − 𝟔𝟎 ∙ 〈𝒙 − 𝟐〉𝟐 − ∙ 〈𝒙 − 𝟒〉𝟑 − ∙ 〈𝒙 − 𝟔〉𝟒 + ∙ 〈𝒙 − 𝟗〉𝟒 + ∙ 〈𝒙 − 𝟏𝟐〉𝟑 + 𝟖𝟏𝟏, 𝟒𝟑𝟕𝟓 ∙ 𝒙
𝟔 𝟔 𝟒 𝟒 𝟔

𝒅𝒗 𝟕𝟑, 𝟐𝟓 𝟒𝟓 𝟔𝟏, 𝟐𝟓
(𝑬 ∙ 𝑰) ∙ = (𝑬 ∙ 𝑰) ∙ 𝜽 = ∙ 〈𝒙 − 𝟎〉𝟐 − 𝟏𝟐𝟎 ∙ 〈𝒙 − 𝟐〉𝟏 − ∙ 〈𝒙 − 𝟒〉𝟐 − 𝟓 ∙ 〈𝒙 − 𝟔〉𝟑 + 𝟓 ∙ 〈𝒙 − 𝟗〉𝟑 + ∙ 〈𝒙 − 𝟏𝟐〉𝟐 + 𝟖𝟏𝟏, 𝟒𝟑𝟕𝟓
𝒅𝒙 𝟐 𝟐 𝟐

Interesses relacionados